Inhibitor-Decorated Polymer Conjugates Targeting Fibroblast Activation Protein - Dvořáková, Petra; Bušek, Petr; Knedlík, Tomáš; Schimer, Jiří; Etrych, Tomáš; Kostka, Libor; Stollinová Šromová, Lucie; Šubr, Vladimír; Šácha, Pavel; Šedo, Aleksi; Konvalinka, Jan (Journal of medicinal chemistry, 2017)
Proteases are directly involved in cancer pathogenesis. Expression of fibroblast activation protein (FAP) is upregulated in stromal fibroblasts in more than 90% of epithelial cancers and is associated with tumor progression. FAP expression is minimal or absent in most normal adult tissues, suggesting its promise as a target for the diagnosis or treatment of various cancers. Here, we report preparation of a polymer conjugate (an iBody) containing a FAP-specific inhibitor as the targeting ligand. The iBody inhibits both human and mouse FAP with low nanomolar inhibition constants but does not inhibit close FAP homologues dipeptidyl peptidase IV, dipeptidyl peptidase 9, and prolyl oligopeptidase. We demonstrate the applicability of this iBody for the isolation of FAP from cell lysates and blood serum as well as for its detection by ELISA, Western blot, flow cytometry, and confocal microscopy. Our results show the iBody is a useful tool for FAP targeting in vitro and potentially also for specific anticancer drug delivery.
Keywords: hmotnostní spektrometrie s elektrosprejovou ionizací; serinové endopeptidasy; Gelatinases; lidé; Serine Endopeptidases; průtoková cytometrie; ELISA; Cell Line, Tumor; endopeptidasy; Flow Cytometry; Enzyme-Linked Immunosorbent Assay; Microscopy, Confocal; myši; Humans; Mice; Blotting, Western; western blotting; Polymers; membránové proteiny; zvířata; polymery; Endopeptidases; Membrane Proteins; Animals; nádorové buněčné linie; želatinasy; konfokální mikroskopie; Spectrometry, Mass, Electrospray Ionization